The Bactericidal Tandem Drug, AB569: How to Eradicate Antibiotic-Resistant Biofilm Pseudomonas aeruginosa in Multiple Disease Settings Including Cystic Fibrosis, Burns/Wounds and Urinary Tract Infections - Hassett, Daniel J.; Kovall, Rhett A.; Schurr, Michael J.; Kotagiri, Nalinikanth; Kumari, Harshita; Satish, Latha (Frontiers in Microbiology, 2021)
The life-threatening pandemic concerning multi-drug resistant (MDR) bacteria is an evolving problem involving increased hospitalizations, billions of dollars in medical costs and a remarkably high number of deaths. Bacterial pathogens have demonstrated the capacity for spontaneous or acquired antibiotic resistance and there is virtually no pool of organisms that have not evolved such potentially clinically catastrophic properties. Although many diseases are linked to such organisms, three include cystic fibrosis (CF), burn/blast wounds and urinary tract infections (UTIs), respectively. Thus, there is a critical need to develop novel, effective antimicrobials for the prevention and treatment of such problematic infections. One of the most formidable, naturally MDR bacterial pathogens is Pseudomonas aeruginosa (PA) that is susceptible to nitric oxide (NO), a component of our innate immune response. First, we discuss how NO therapeutics may be able to target problematic infections in each of the aforementioned infectious scenarios. Second, we describe a recent discovery, a novel drug known as AB569, that is capable of forming a “time release” of NO from S-nitrosothiols (RSNO). AB569, a bactericidal tandem consisting of acidified NaNO2 (A-NO2-) and Na2-EDTA, is capable of killing all pathogens that are associated with the aforementioned disorders. Third, we described each disease state in brief, the known or predicted effects of AB569 on the viability of PA, its potential toxicity and highly remote possibility for resistance to develop. Finally, we conclude that AB569 can be a viable alternative or addition to conventional antibiotic regimens to treat such highly problematic MDR bacterial infections for civilian and military populations, as well as the economical burden that such organisms pose.